Spatial spillover and threshold effects of digital rural development on agricultural circular economy growth - Xu, Jiehua (Frontiers in Sustainable Food Systems, 2024)
The infusion of digital technologies imparts impetus to the development of agricultural circular economy. Study focuses on the nexus of digital rural development, agricultural circular economy growth, employing entropy, Critic, and TOPSIS models to calculate the evolution of agricultural circular economy from 2011 to 2021. Furthermore, the temporal and spatial dynamics of agricultural circular economy development are explored. In addition, spatial Durbin models and threshold models are utilized to explore the spatial spillover effects of digital rural development on agricultural circular economy, and the threshold characteristics of agricultural circular economy with varying levels of digital rural development. The research findings reveal that arable land area, forest coverage, and mechanization play pivotal roles in shaping the trajectory of rural circular economy development. The synthetical index of rural circular economy development shows a consistent yearly increment, yet pronounced regional disparities exist, reflecting an olive-shaped distribution with dual cores in Heilongjiang and Chongqing and a more prominent central. The implementation of digital rural not only elevates the local agricultural circular economy, but also demonstrates conspicuous spatial spillover effects on neighboring regions. The relationship between digital rural development and agricultural circular economy growth is characterized by a singular threshold effect. Pre-and post-threshold, the promotive impact of digital rural development rises from 0.048 to 0.058. Building upon these findings, policy recommendations are formulated to guide future endeavors in this domain.